Diurnal Variation in Visual Simple Reaction Time between and within Genders in Young Adults: An Exploratory, Comparative, Pilot Study - Hanumantha S; Ashwin Kamath; Rajeshwari Shastry (The Scientific World Journal)
Simple reaction time (SRT) is the minimum time required to respond to a stimulus; it is a measure of processing speed. Our study aimed to determine the variation in visual SRT with time among individuals of the same gender and between genders. We carried out a prospective, parallel group, pilot study involving ten male and ten female medical students aged 18–25 years. After obtaining written informed consent, the participants were familiarized with the procedures, and each completed a single practice session of a computerized visual SRT which was administered using Psychology Experiment Building Language Version 2.0 software. On a predetermined day, the participants completed the exercise at 10 a.m., 1 p.m., and 5 p.m. The results showed no statistically significant difference in SRT based on time of day between genders (χ2(2) = 4.300, p=0.116) as well as within gender (males (χ2(2) = 0.600, p=0.741); females (χ2(2) = 5.000, p=0.082). Our study showed that visual SRT does not change significantly at different times of the day and within and between genders. Intraindividual variations in visual SRT can mask the presence of a small but significant difference; hence, further studies are warranted.